The configurations of education in families, schools, and communities and the relationship with the quality of education at junior high schools in Bantul Regency - Setya Raharja; Suyata Suyata; Siti Partini Suardiman (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2018)
This study aims at finding the configuration pattern in education that exists among families, schools and social community and determining the quality of education which affects the high quality of education. This study implements phenomenological-qualitative approach carried out in three schools in Bantul regency. The respondents of the research were the principals, teachers, students, school committee, and parents. The data were obtained through in-depth interview, observation and documentation study which were analyzed qualitatively. The result of the research shows that the pattern of educational configuration is formed by the variations of school’s implementation of responsibilities carried out separately and consecutively in a family, schools and a social community. The quality of education at the level of school system is considered better compared to that of individuals and it also varies based on the school’s condition. The pattern of configuration of the educational responsibility aspect is related to the quality of education itself. The pattern does affect the level of the quality of the education if the family, schools and the social community do the responsibility separately, consecutively and consistently without being affected by any distractor.